The Incidence of Psychologic Stress following a Fall and Surgical Treatment of Distal Radius Fractures - Schindelar, Lili; Katt, Brian; Townsend, Clay; Imbergamo, Casey; Takei, Robert; Beredjiklian, Pedro (Journal of Wrist Surgery, 2021)
Background and Purpose Experiencing a fall and a subsequent distal radius fracture can have a major impact not only on patients' physical function, but also on their emotional state. The purpose of this project was to describe the prevalence of fear of falling (FoF) and posttraumatic stress disorder (PTSD) following surgically managed distal radius fractures due to a fall.Methods Patients who underwent surgery for a distal radius fracture due to a fall were identified by a database query. Patients were divided into three groups based on time from surgery: 0 to 2 weeks (acute), 3 to 6 months (mid-term), and 12 to 15 months (long-term). FoF was measured using the Falls Efficacy Scale-International (FES-I) questionnaire. PTSD was measured using the PTSD Checklist for Diagnostic and Statistical Manual of Mental Disorders (DSM) Text Revision-5 (PCL-5) questionnaire. A total of 239 patients who met inclusion criteria were consented via phone and completed the emailed surveys.Results FES-I scores were significantly higher in the acute group versus the long-term group (p = 0.04). High concern for FoF was observed in 63% (19/30) of patients in the acute group, in 35% (14/40) in the mid-term group (p = 0.019 vs. acute), and in 19% (8/42) in the long-term group (p < 0.001 vs. acute). Probable PTSD was observed in 2.3% (1/44) of patients in the acute group, in 4.8% (2/42) in the mid-term group, and in 7.3% (3/41) in the long-term group.Conclusion Patients who undergo surgical fixation of a distal radius fracture due to a fall are subject to FoF and PTSD symptoms. To maximize postoperative outcomes, it is important for surgeons to be aware of these psychological effects and know how to screen for them.Level of Evidence This is a Level III study.
Keywords: fear of falling; distal radius fracture; posttraumatic stress disorder